Pedagogi Hati dan Pengembangan Jati Diri Spiritual - Johanis Ohoitimur; Anselmus Jamlean (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2023)
In recent years the charism and the spirituality of Jules Chevalier have been continously promoted by the Cor Novum Team from Issoudun, France, and then Cor Vitae Team from Manila, the Philipines. More and more lay people and religious women and men participate in the spirituality of the heart programs. This is indeed a blessing for all members of the Chevalier family. We seek deeper understanding of Chevalier’s charism and spirituality, but more importantly a way of life which roots in God’s love in human heart. This short article is intended to introduce the so-called pedagogy of the heart. It clarifies the meaning of the heart, and underlines that reflection or apperception is methodologically an absolute condition for those who wish to live daily the spirituality of the heart.